2010
DOI: 10.2807/ese.15.42.19693-en
|View full text |Cite
|
Sign up to set email alerts
|

Urban–rural differences of age- and species-specific campylobacteriosis incidence, Hesse, Germany, July 2005 – June 2006

Abstract: Binary file ES_Abstracts_Final_ECDC.txt matches

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 28 publications
(44 reference statements)
2
8
0
Order By: Relevance
“…In contrast, this effect was not observed or even reversed in older persons (Figure 4). Our result is consistent with a study conducted in the German federal state of Hesse from 2005–2006 [30] that examined the association between age-specific Campylobacter incidence and the degree of urbanicity of the district of the place of residence also showing an increased incidence in children living in rural areas. This has also been demonstrated by other studies in Europe [23,31].…”
Section: Discussionsupporting
confidence: 92%
“…In contrast, this effect was not observed or even reversed in older persons (Figure 4). Our result is consistent with a study conducted in the German federal state of Hesse from 2005–2006 [30] that examined the association between age-specific Campylobacter incidence and the degree of urbanicity of the district of the place of residence also showing an increased incidence in children living in rural areas. This has also been demonstrated by other studies in Europe [23,31].…”
Section: Discussionsupporting
confidence: 92%
“…In the final adjusted model, in zip codes that are characterized as 100% rural by the U.S. Census the incidence rate of Campylobacter infection was 6 times that of zip codes that are less than 0.9% rural (IRR=6. 18;) ( Table 2). In zip codes that contain broiler chicken operations, the incidence rate of campylobacteriosis was 1.45 times that of zip codes that do not contain broiler operations (IRR=1.…”
Section: Impact Of Community-level Environmental Factorsmentioning
confidence: 99%
“…Significant associations between living in rural areas and risk of campylobacteriosis also have been identified in Europe and Canada [16][17][18] . Moreover, a specific feature of rural environments, animal density, has been identified as a significant predictor of…”
Section: Introductionmentioning
confidence: 99%
“…The numbers of reported cases for the whole of Germany indicate an overall decrease in the number of Salmonella cases and an increase in the number of Campylobacter cases. Campylobacteriosis is the most commonly reported gastrointestinal disease in the European Union [ 13 ], whereas in the US, FoodNet reported that the incidence of Campylobacter infections from 1996 to 2005 had declined so much that Salmonella infections currently outnumber those caused by Campylobacter . The incidence of Campylobacter infections in Germany is about 80/100,000 and is significantly higher than that of salmonellosis [ 14 ].…”
Section: Discussionmentioning
confidence: 99%